2021
DOI: 10.2147/opth.s291790
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Ophthalmology Practices and Attitudes in the Philippines in Light of the COVID-19 Pandemic: A Survey

Abstract: Background: The Severe Acute Respiratory Syndrome Coronavirus 2 (COVID-19) pandemic has limited patient access to outpatient care, prompting many clinicians to incorporate telemedicine in their practice. This study aims to explore the impact of the pandemic on the use of tele-ophthalmology in the Philippines. Methodology: A 30-item online survey on practices and attitudes related to teleophthalmology was sent to ophthalmologists and ophthalmologists-in-training all over the Philippines. Results: A total of 327… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…However, only 16% reported confidence in handling their patients through telemedicine. This finding is lower than the reported result of Azarcon and colleagues 9 where they found that 47% of practicing ophthalmologists and ophthalmologists-in-training felt confident with discussing a patient's condition remotely. The lower confidence reported in our survey may be attributed to the fact that all respondents were ophthalmologists-intraining whereas Azarcon et al's participants were mostly (70%) practicing ophthalmologists.…”
Section: Clinical Activitycontrasting
confidence: 68%
“…However, only 16% reported confidence in handling their patients through telemedicine. This finding is lower than the reported result of Azarcon and colleagues 9 where they found that 47% of practicing ophthalmologists and ophthalmologists-in-training felt confident with discussing a patient's condition remotely. The lower confidence reported in our survey may be attributed to the fact that all respondents were ophthalmologists-intraining whereas Azarcon et al's participants were mostly (70%) practicing ophthalmologists.…”
Section: Clinical Activitycontrasting
confidence: 68%
“… 3 In a survey done in the Philippines, ophthalmologists reported an increased usage in tele-ophthalmology from 53% to 90% at the time of the COVID-19 pandemic. 4 Although high percentages were noted, examination of the eye remotely is still difficult due to limitations in examination procedures such as accessibility, interpretation of results, and availability of testing materials at home. One of the difficulties in telemedicine is visual acuity testing, which is the cornerstone of any eye examination.…”
Section: Introductionmentioning
confidence: 99%
“…Consultations through telemedicine are particularly useful for screening patients for red flag ophthalmic signs and symptoms to determine which ones truly need a face-to-face consult. 15,16 The main limitation of retinal telemedicine in the current setting is that most established guidelines still require patients to have retinal imaging done at an eye center -a situation that is difficult in a quarantine setting. The development of home-based retinal imaging is a major limiting factor.…”
Section: Discussionmentioning
confidence: 99%